Foreign Direct Investment in the New European Union Member States and Developing Countries of Asia under Conditions of the Global Financial and Economic Crisis: Comparative Aspects; Bezposŕednie inwestycje zagraniczne w nowych krajach członkowskich Unii Europejskiej i rozwijajacych sie krajach Azji w warunkach globalnego kryzysu finansowego i ekonomicznego. Aspekty komparatywne - Janina Witkowska (Comparative Economic Research. Central and Eastern Europe, 2009)
The objective of this article is a comparative analysis of the changing position of new European Union member states and the developing countries of Asia in global and regional FDI flows as well as an assessment of the impact of the global crisis on the position of these regions and selected countries in terms of FDI. The analysis encompasses European Union member states that received membership as a part of the enlargement of 2004 and 2007 as well as the developing sub-regions of Asia-i.e. East, South-East, and South Asia. The conducted analysis demonstrates that the position of the developing countries of Asia is significantly stronger than that of the new European Union member states, which is mainly determined by the scale of the economies of countries such as China and India. Subject to conditions of global crisis, Asia and Oceania as a whole noted growth in the inflow of FDI in 2008 by almost 17%, where the European Union member states saw a 2% fall. The situation inside the analyzed regions is extremely varied in terms of noticeable effects of the crisis in the FDI sphere. It is dependent on not only processes of economic growth, but also on the character of investments made in the individual countries and sub- regions as well as motives behind the actions of investors. – – Celem niniejszego artykułu jest analiza poroẃnawcza zmieniajacej sie pozycji nowych krajoẃ członkowskich UE i rozwijajacych sie krajoẃ Azji w globalnych i regionalnych przepływach BIZ, a takzė ocena wpływu globalnego kryzysu finansowego na pozycje tych regionoẃ i wybranych krajoẃ w zakresie BIZ. Analiza zostały objete kraje członkowskie UE, ktoŕe uzyskały członkostwo w ramach rozszerzenia z 2004r. i 2007r. oraz rozwijajace sie sub-regiony Azji, tj. Azja Wschodnia, Południowo- Wschodnia i Południowa. Z przeprowadzonej analizy wynika, zė pozycja rozwijajacych sie krajoẃ Azji w globalnych przepływach kapitałowych jest znacznie silniejsza nizṅowych krajoẃ członkowskich UE, o czym decyduje skala gospodarek takich krajoẃ jak Chiny i Indie. W warunkach globalnego kryzysu, Azja i Oceania jako całosćódnotowały w 2008r. wzrost napływu BIZ o prawie 17%, a nowe kraje członkowskie UE - spadek o 2%. Sytuacja wewnatrz analizowanych regionoẃ jest wysoce zroźṅicowana pod wzgledem odczuwalnych skutkoẃ kryzysu w sferze BIZ. Jest to zalezṅe nie tylko od procesoẃ wzrostu gospodarczego, ale takzė od charakteru inwestycji lokowanych w poszczegoĺnych krajach i sub-regionach oraz motywoẃ, jakimi kieruja sie inwestorzy.
Keywords: 330